PSIKOLOGI ISLAM SEBAGAI ILMU PENGETAHUAN: Epistemologi & Pengembangan di Masa Depan - Hasan, Aliah B. Purwakania (Jurnal Psikologi, 2012)
This paper aims to provide an overview of the progress of Islamic Psychology as a science is the result of the integration between Islam and psychology. Islamic psychology has a specific scientific method, which is a combination of reading and kauniyah kauliyah paragraph. With this method of Islamic Psychology Scientifics has a slightly different character to the other sciences put the value- free objectivity and total empiricism. This paper also discusses the importance of efforts to improve the quality and quantity of research and scientific publications with the mapping to the overall outcome of thought and research, resulting in the development of a cumulative and do not spin in place. In this case the role of Islamic Psychology Association in collaboration with universities that are interested in this field is very important, especially in improving the competence of the resources of scientists and psychologists in this field through the entire education pathway.